2007
DOI: 10.1136/adc.2006.096479
|View full text |Cite
|
Sign up to set email alerts
|

Severe retinopathy of prematurity in infants <30 weeks' gestation in New South Wales and the Australian Capital Territory from 1992 to 2002

Abstract: In infants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
6
23
0
1
Order By: Relevance
“…The importance of the influence of extreme prematurity on the incidence of severe ROP is also supported by the studies of Todd et al [15] and Haines et al [18] . Todd et al [15] found an increase in severe ROP in infants ! 25 weeks' gestation but a significant decrease in infants of 25-26 weeks' gestation.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The importance of the influence of extreme prematurity on the incidence of severe ROP is also supported by the studies of Todd et al [15] and Haines et al [18] . Todd et al [15] found an increase in severe ROP in infants ! 25 weeks' gestation but a significant decrease in infants of 25-26 weeks' gestation.…”
Section: Discussionsupporting
confidence: 66%
“…Incidence of overall ROP was not available in these studies. Todd, however, found no [15] . No data on incidence of overall ROP were available.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1 As survival of the very preterm infant has increased in recent years, the incidence of severe ROP, which is associated with vision loss, is reported to be increasing. [2][3][4] Among factors suggested to have association with ROP, low gestational age and low birth weight are the strongest and most consistently identified risk factors. 1,5,6 As gestational age is a major contributor of birth weight and these two factors closely correlate, the respective causal relationship in the pathogenesis of ROP and the superiority between the two factors are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Children with the progressive ROP necessitate cryotherapy or laser photocoagulation. There are papers which report either increase or decrease in the number of infants treated for ROP in the last years [2,3].…”
Section: Introductionmentioning
confidence: 97%